2009
DOI: 10.1037/a0014528
|View full text |Cite
|
Sign up to set email alerts
|

The perfectionism model of binge eating: Tests of an integrative model.

Abstract: This study proposes, tests, and supports the perfectionism model of binge eating (PMOBE), a model aimed at explaining why perfectionism is related to binge eating. According to this model, socially prescribed perfectionism (SPP) confers risk for binge eating by generating exposure to 4 triggers of binge episodes: interpersonal discrepancies, low interpersonal esteem, depressive affect, and dietary restraint. In testing the PMOBE, a daily diary was completed by 566 women for 7 days. Predictions derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
196
10
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(227 citation statements)
references
References 146 publications
15
196
10
6
Order By: Relevance
“…In line with previous research demonstrating the role of EC perfectionism as a risk factor for eating disorder symptoms (DiBartolo et al, 2008;Soenens et al, 2008) and for bulimic symptoms in particular (Sherry & Hall, 2009), we found only EC (and not PS) perfectionism to predict increases in bulimic symptoms. This finding suggests that being overly critical of one's own behavior and performance increases the risk to experience bulimic symptoms two years later.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In line with previous research demonstrating the role of EC perfectionism as a risk factor for eating disorder symptoms (DiBartolo et al, 2008;Soenens et al, 2008) and for bulimic symptoms in particular (Sherry & Hall, 2009), we found only EC (and not PS) perfectionism to predict increases in bulimic symptoms. This finding suggests that being overly critical of one's own behavior and performance increases the risk to experience bulimic symptoms two years later.…”
Section: Discussionsupporting
confidence: 79%
“…This is unfortunate because such an examination is necessary to gain a better understanding of the underlying mechanisms through which perfectionism affects eating-disordered behaviors and attitudes. One notable exception is a recent study by Sherry and Hall (2009) in which a mediation model was introduced entailing interpersonal discrepancies, low interpersonal esteem, depressive affect, and dietary restraint as possible mediating variables between socially prescribed perfectionism and binge eating. Results of this study suggest that socially prescribed perfectionism serves as a risk factor for binge eating through its effect on each of the four tested mediators.…”
Section: Perfectionism and Eating Disorder Symptomsmentioning
confidence: 99%
“…By examining need frustration as a global mechanism, we aimed to add to previous studies examining either other global (e.g., depressive symptoms; self-esteem; interpersonal discrepancy and esteem) (Sherry & Hall, 2009) or more specific mechanisms (e.g., thin ideal internalization and dietary restraint) (Boone et al, 2011) involved in the development of binge eating. Both the more global and the more specific approach are of value as they likely provide complementary information.…”
Section: Perfectionism and Psychological Need Frustration 24mentioning
confidence: 99%
“…Daily diary studies have shown that perfectionism (Boone, Soenens, Thanasis, et al, 2012), need frustration (Verstuyf et al, 2013), and binge eating (Sherry & Hall, 2009) fluctuate from day to day within individuals, and have shown that they influence each other during the course of one day. However, no study has examined the interrelations between these constructs simultaneously at the level of daily fluctuation.…”
Section: Limitations and Research Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation